Acoustic target strength measurement of striped goatfish (Upeneus vittatus) - Syahrul Purnawan; Henry M Manik; Totok Hestirianoto; Khairul Amri; Agung Prasetiawan; Win Alfi Syahrin; Siddiq Husaini Husal; Said M Faaris; Aqil Hawari (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
The Striped Goatfish (Upeneus vittatus) is a demersal species of significant ecological and economic value, particularly for small-scale fisheries in Aceh Province. Accurate biomass estimation and species identification in hydroacoustic surveys rely heavily on precise target strength (TS) reference values. This study aimed to establish reference TS values for U. vittatus by examining the relationship between TS and fish morphology. Specimens collected from northern Aceh waters were measured for total length (TL: 17.328.3 cm) and weight (W, g). TS measurements were conducted using a single-beam echosounder (Simrad EK15) operating at 200 kHz with a pulse duration of 0.16 ms in a controlled water-tank environment. This approach enabled the assessment of TS variability across specimens with different TLs. A robust relationship between TL and weight revealed positive allometric growth (b = 3.2932, R = 0.94) in the study. Furthermore, TS analysis demonstrated a logarithmic increase with TL (R = 0.6459), in alignment with theoretical predictions. These findings contribute to more accurate biomass estimation and support sustainable management strategies for U. vittatus populations in northern Aceh, Indonesia. Future research should encompass a broader range of fish sizes and incorporate additional biological variables to refine TS prediction models further.Keywords:GoatfishAcehLWRTSMullidae